PROBLEMATIKA PELAKSANAAN LELANG PADA PANGAMBEK DI TEMPAT PELELANGAN IKAN (TPI) PAITON PROBOLINGO (PERSPEKTIF EKONOMI ISLAM) - Moh Ainur Rizqi; Zainur Ridho (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2021)
This paper aims to find out the problem of the auction process at the fish auction place in Paiton Probolinggo. The method used is to use descriptive qualitative methods in the collection technique through active observation, interviews with the head of the fish management office, middlemen and fishermen for documentation through the required documents. . The results of his research The fish auction place in Paiton in the practice of auctioning by wholesalers/panganmbek as providers of capital as a binder of auctions occurs when fishermen lack access to capital. The provision of capital begins with the provision of money from the middleman (bakul) to the skipper of the ship. The money was given with an agreement that the fish caught were sold to him. However, the money is actually a bond money for the fish caught later produced by fishermen. The catch of fish is directly given to the buyer (bakul) who has given the money without going through the auction process without involving the Paiton TPI office so that the retribution does not go well. In the auction practice at TPI Paiton, namely the attachment of fishermen to capital providers or middlemen in the auction process in Islam, it is also called muzayadah derived from the word zayadah which means adding-adding, namely bidding higher than others.